Analysis of Technical Performance of PSS2 Based on An Active Power Oscillation Accident of generator. Issue 1 (June 2021) - Zhang, Guangtao; Liang, Hao; Xie, Huan; Wu, Tao; Shi, Yang; Zhao, Yan; Yan, Yian; Guo, Zhifeng; Guo, Jian; Liu, Lili; Tan, Qibang
Abstract: Low frequency oscillation in power system has become the main factor limited the development of power grid in China. Taking the generator power oscillation accident caused by PSS abnormal operation in a gas power plant of China as an example, the accident process is introduced in detail, and the causes of the accident are preliminarily discussed through the analysis of related data. The generator model is established with RTDS platform, then the influences of the rotational inertia, and speed acquisition methods of the unit and setting of the swing reactance on generator PSS(Power System Stabilizer) suppressing power oscillation effect are simulated and analyzed. According to the research results, the accident causes are further analyzed, and relevant suggestions are given for how to avoid such accidents.